Chemical homogeneity of wide binary systems: an approach from near-infrared spectroscopy - Lim, Dongwook; Koch-Hansen, Andreas; Hong, Seungsoo; Chun, Sang-Hyun; Lee, Young-Wook (The astronomical journal, 2024)
Wide binaries, with separations between the two stars from a few au to more than several thousand au, are valuable objects for various research topics in Galactic astronomy. As the number of newly reported wide binaries continues to increase, studying the chemical abundances of their component stars becomes more important. We conducted high-resolution near-infrared (NIR) spectroscopy for six pairs of wide binary candidates using the Immersion Grating Infrared Spectrometer at the Gemini-South telescope. One pair was excluded from the sample due to a significant difference in radial velocity between its component stars, while the remaining five pairs exhibited homogeneous properties in 3D motion and chemical composition among the pair stars. The differences in [Fe/H] ranged from 0.00 to 0.07 dex for these wide binary pairs. The abundance differences between components are comparable to the previous results from optical spectroscopy for other samples. In addition, when combining our data with literature data, it appears that the variation of abundance differences increases in wide binaries with larger separations. However, SVO 2324 and SVO 3206 showed minimal differences in most elements despite their large separation, supporting the concept of multiple formation mechanisms depending on each wide binary. This study is the first approach to the chemical properties of wide binaries based on NIR spectroscopy. Our results further highlight that NIR spectroscopy is an effective tool for stellar chemical studies based on equivalent measurements of chemical abundances from the two stars in each wide binary system.
Gesehen am 29.01.2024